Higher education leadership : professionalism in Finnish higher education in departmental level - Nasrolahi, Mohsen (2019)
Achieving a highly quality educational system without taking the issue of leadership into consideration would be unattainable. Academic leadership has gained more attention during the past few decades and considered as one of the essential factors in the success of any educational institution. Finland, as one of the most leading countries in the field of education, is regarded as an example of a successful school leadership system. However, the purpose of this research is to study Finnish academic leadership and reveal how academic leaders in Finland manage to end up with leadership positions. The question that this research explores is to what extent academic leaders in Finland are specialized and trained for leadership posts. The impacts of leadership expertise and its absence are also examined in this research. In order to collect the required data, eight departments in two Finnish universities were selected, and the administrative head of each department was interviewed. In this qualitative study, the data was analysed using a content analysis approach. The data from the semi-structured interviews provide insight into academic leadership sphere in Finnish higher education institutions. The findings from this study highlight the significance of training higher education leaders and points to the challenges resulting from a lack of expertise and training.